Pengaruh Bentuk Permukaan Absorber Pelat Terhadap Produktivitas dan Efisiensi Solar Still - purbo suwandono; nova risdiyanto ismail (Polinema Press, Politeknik Negeri Malang, 2019)
Based on previous research, research on the development of solar distillation models is needed. Development of absorbent plates (absorber) using cast concrete material with fin, wave and flat models as a comparison. The fin and wave absorber plates can expand the surface, thereby increasing the intensity of solar radiation received by the absorber. Cast concrete is a porous material that can absorb sea water and make a thin layer, making it easier for the evaporation process and can improve solar distillation performance In this study using the experimental method. Solar still research by examining the surface of a cast concrete absorber plate. The surface of the absorbent plate used is the fin, wave and flat / conventional models. Cast concrete uses stone, iron sand, PCC cement and water. The study used variations in water volume The research resulted in the surface shape of the fin model can increase the productivity of fresh water and the efficiency of solar still using a plate absorbent fin model is higher than the wave and flat models. A smaller volume of sea water can increase productivity higher than a larger volume of sea water.